Pigmented Oral Lesions: A Multicenter Study - Dhanuthai, Kittipong; Theungtin, Natchaya; Theungtin, Natnicha; Thep-akrapong, Pantira; Kintarak, Sompid; Klanrit, Poramaporn; Chamusri, Nutchapon; Sappayatosok, Kraisorn (European Journal of Dentistry, 2021)
Objectives The aim of this study was to determine the prevalence and clinical features of pigmented oral lesions from Thailand.Materials and Methods Biopsy records of the Department of Oral Pathology, Chulalongkorn University, Department of Oral Diagnosis, KhonKaen University, Department of Oral Biology and Oral Diagnostic Sciences, Chiangmai University, Department of Stomatology, Prince of Songkla University, and Rangsit University were reviewed for oral pigmented lesions diagnosed during 1999 to 2019. Demographic data were culled from the biopsy records. Ages of the patients were subdivided into 10-year intervals. Locations of the lesions were classified as gingiva, labial/buccal mucosa, palate, floor of the mouth, tongue, as well as the combination of sites. Data were analyzed by descriptive statistics using SPSS version 20.0.Results Of the 47,175 accessioned cases, 241 cases (0.51%) were diagnosed in the category of pigmented oral lesions. The age of the patients ranged from 1 month to 88 years with the mean ± standard deviation = 38.74 ± 20.96 years. Regarding gender, 172 patients (71.37%) with pigmented lesions were females, while 69 patients (28.63%) were males. The female-to-male ratio was 2.49:1. The majority of the pigmented lesions were encountered at the gingiva (29.88%) followed by labial/buccal mucosa (26.97%), palate (14.94%), lip (10.79%), alveolar mucosa (9.54%), and others (7.88%), respectively. The three most common pigmented oral lesions in the present study were nevus (39.83%), followed by melanotic macule (28.63%) and amalgam tattoo (17.43%), respectively.Conclusions The most common pigmented oral lesion in the present study is nevus. Demographic data of the patients in the present study are in accordance with previous studies with minor differences. Even though pigmented lesions of the oral cavity constitute a small portion of the oral pathology biopsies, accurate diagnosis is important since there is an overlap in clinical appearance of benign pigmented lesions and melanoma.
Keywords: clinical features; pigmented lesions; prevalence; Thailand